LEGAL ANALYSIS OF THE PROBLEM OF NON-PERFORMING LOANS IN INDONESIA BASED ON BANKING LAW PERSPECTIVE - POLLATU, STACEY KHARIN CHELINE; Ratih Damayanti (Universitas Negeri Semarang, 2025)
People's living and financial needs are increasing, causing people to have to try hard to meet these needs in various ways. The development of the banking sector in Indonesia is here to offer changes and benefits to society, especially regarding financial needs which are essentially always related to social life. One of the financial facilities that attracts public interest and is considered to make transactions easier, increase assets or develop a business is credit services. Credit is a loan originating from a bank to its customers with a return of principal and interest within a specified time period. However, in reality, this facility is actually vulnerable to the emergence of other problems such as bad credit which occurs between the creditor, in this case the bank, and the customer or in this case the debtor. Bad credit is a problem that is quite important to deal with because it not only affects the economic system as a whole. There are many factors that cause this dispute, both from creditors and debtors, so the aim of this research is to carry out an in-depth legal analysis regarding existing regulations regarding the problem of bad credit in the banking sector and the role of related institutions in resolving this problem and providing definite legal protection.